Strawberry monocropping: Impacts on fruit yield and soil microorganisms - Guerrero Molina, María Fernanda (2017)
The objective of this work was to explore the impacts of intensive strawberry monocropping during five years on the fruit-yield and on the microbial soil activity and composition. Field trials were performed in two plots: P1(a soil with five years of consecutive strawberry cropping), and P2 (a soil with just one year of strawberry cropping). Fruit-yield was quantified; total microorganisms and four functional groups (cellulolytics, nitrogen-fixers, phosphate solubilizers, and siderophores producers) were quantified, isolated and characterized in both plots. Total microbial activity was assessed by the hydrolysis of fluorescein-diacetate and soil respiration methods. As results, in P1, a 51 % decrease in fruit-yield was observed, while in P2 it was closer to the yield obtained in P1 during the first and second year of cultivation. Total microbial number and activity were 23 % and 70 % lower in P1 than in P2 at the end of the cropping, respectively. In general, the quantity of total culturable microorganisms and the functional groups analyzed were significantly higher in P2 than in P1 (p< 0.05).The most prevailing bacteria putatively identified were Cellulosimicrobium cellulans, Paenibacillus sp., Azospirillum brasilense, and Burkholderia sp. According to our results, the intensive cultivation of strawberry for several years in the same field exerted a negative impact on the soil quality, affecting the native microbial population, which might be linked to the fruit yield decline.